Formation of similarity criteria for physical objects and processes based on NonDimCritFormer 1.0 computer program - I. M. Tsibirova (Advanced Engineering Research, 2019)
Introduction. The problem of adequate modeling of physical processes and objects is an urgent task of modern science. Automation of work in this area increases the accuracy of modeling and saves money on full-scale modeling of objects under study. The research objective was to create a computer program that would automatically form dimensionless similarity criteria based on the initial set of parameters.Materials and Methods. The calculation algorithm is based on к-theorem of similarity theory and the basic provisions of the dimensional theory.Research Results. The computer program is developed. It enables to get all the theoretically possible similarity criteria for the simulation of the physical process or object of interest. Discussion and Conclusions. The results obtained can be used in the industrial and scientific modeling of physical objects of research, calculation of new similarity criteria, solving problems of describing complex processes, etc.